The Impact of Digital Transformation of Public Services on Economic Growth A Comparative Study - شريقي طرفة (Latakia University Journal - Economic and Legal Sciences Series, 2025)
This study aims to assess the impact of digital transformation, specifically e-government development, on economic growth in three countries: Estonia, India, and Rwanda. Using data on the E-Government Development Index and Gross Domestic Product for these countries, a statistical analysis was conducted to determine the relationship between the two variables. The results showed a significant positive correlation between the E-Government Development Index and GDP in both Estonia and Rwanda, while no such relationship was found in India. These differences were explained based on several factors, including digital infrastructure, population size and geographic diversity, political will, digital literacy and skills, and socio-economic challenges. This study seeks to provide insights into the factors that influence the success of digital transformation and promote economic growth.